2013
DOI: 10.1523/jneurosci.0663-13.2013
|View full text |Cite
|
Sign up to set email alerts
|

Parvalbumin-Expressing Inhibitory Interneurons in Auditory Cortex Are Well-Tuned for Frequency

Abstract: In the auditory cortex, synaptic inhibition is known to be involved in shaping receptive fields, enhancing temporal precision, and regulating gain. Cortical inhibition is provided by local GABAergic interneurons, which comprise 10 -20% of the cortical population and can be separated into numerous subclasses. The morphological and physiological diversity of interneurons suggests that these different subclasses have unique roles in sound processing; however, these roles are yet unknown. Understanding the recepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
188
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 212 publications
(207 citation statements)
references
References 80 publications
19
188
0
Order By: Relevance
“…These major types of GABAergic interneurons expressing PV and SOM are argued to contribute to cortical signal representation, local and system coordination, and experience-dependent plasticity (14,18,22,(54)(55)(56)(57). For example, recent studies have shown that PV+ neurons in the auditory cortex have markedly faster response latencies than PV-neurons, indicating their critical roles in regulating the temporal precision of cortical responses (55). Cortical SOM+ neurons, on the other hand, provide delayed and more selective inhibition to modulate the processing of complex stimuli, as in human speech (58).…”
Section: Discussionmentioning
confidence: 99%
“…These major types of GABAergic interneurons expressing PV and SOM are argued to contribute to cortical signal representation, local and system coordination, and experience-dependent plasticity (14,18,22,(54)(55)(56)(57). For example, recent studies have shown that PV+ neurons in the auditory cortex have markedly faster response latencies than PV-neurons, indicating their critical roles in regulating the temporal precision of cortical responses (55). Cortical SOM+ neurons, on the other hand, provide delayed and more selective inhibition to modulate the processing of complex stimuli, as in human speech (58).…”
Section: Discussionmentioning
confidence: 99%
“…PV + neurons in auditory cortex are believed to be involved in regulating the temporal precision of cortical responses instead of shaping frequency tuning, because they usually have faster response latencies and are well tuned for frequency (48). This result may explain the observation that, although training renormalized A1 temporal responses of CTM-exposed rats, it did not restore cortical frequency selectivity to normal.…”
Section: Discussionmentioning
confidence: 99%
“…For PV-PV mice, data were collected using either 445-nm or 520-nm wavelength light to control for nonspecific wavelength effects. Analyses were limited to well-isolated putative pyramidal neurons [see SI Methods for interneuron exclusion criteria and cluster isolation metrics (52)(53)(54)]. Mean firing rates were calculated for each 5-min interval and were analyzed using paired t tests.…”
Section: Methodsmentioning
confidence: 99%